Konsep Pemikiran Ibnu Sina tentang Pendidikan - Susanti, Roza (JOEAI (Journal of Education and Instruction), 2021)
The purpose of this study is to see the role of Ibn Sina who has a very broad influence, not only in the Islamic world, but also in the Western world. The scope of his expertise is quite broad, ranging from medicine, philosophy, Islamic law, to education. This research is a qualitative research which is library research. The results of the study, at this time there has been a decline in morals in various circles, especially among students. So far, the simplistic view that has developed in society considers the decline in the morals, morals and ethics of students to be caused by the failure of religious education in schools. It must be admitted, to a certain extent, religious education learning has certain weaknesses, starting from the very minimal number of hours, educational materials that are too many theories, to educational approaches that tend to rely on cognitive aspects rather than affective and psychomotor aspects of students. . In conclusion, as a philosopher who is very concerned about education issues, Ibn Sina gives a lot of understanding in laying the foundations of Islamic education, which is very valuable and has no small influence on Islamic education today. In education, he attaches great importance to moral education that integrates idealistic values ​​with a pragmatic view. Keywords: Ibn Sina, Concept of Thought, Moral Education